(untitled) (Health Renaissance, 2013)
Background: B P Koirala Institute of Health Sciences (BPKIHS), Dharan, Nepal runs undergraduate medical education program with an innovative, community-oriented/based and integrated MBBS curriculum since 1994, which aims to prepare basic medical graduates appropriate for the country in the twenty-first century. Objective: To examine factors that influence the BPKIHS graduates in selecting their choice of specialty in post-graduation. Methods: A total of 19 factors influential in doctor.s choice of specialty1 assessed on Likert scale of 0-4 (where factor 0=not at all and 4=a great deal) amongst 37 BPKIHSgraduates who were in the pay-roll at the time of study in the BPKIHS (23 junior residents and 14 senior residents/faculty members) through a questionnaire. Results: Intrinsic factors were more influential (81.1%) than extrinsic factors (37.8%) in choosing specialty in residency. Amongst the intrinsic factors, advancement prospects was rated highest (89.1%). Other highly rated intrinsic factors in order were job security prospects (86.4%), prestige of discipline (83.7%), financial prospects (75.6%), intellectual content of the specialty and interest in helping people (73.0%), and appraisal of own skills and aptitudes (64.9%). Amongst the extrinsic factors, the highly rated factors were opportunity to do procedural work and opportunity for research/teaching (83.7% rating factor). Conclusion: No matter what characteristics the medical school curriculum has, the intrinsic factors inculcated into the minds of the graduates based on their own interests seem more influential in choosing a specialty as their career choice. Health Renaissance, January-April 2013; Vol. 11 No.1; 68-73 DOI: http://dx.doi.org/10.3126/hren.v11i1.7606